Comparative study of variational chaos indicators and ODEs' numerical integrators - Darriba, Luciano A. (2012)
Fil: Darriba, Luciano A. Universidad Nacional de la Plata. Facultad de Ciencias Astronómicas y Geofísicas; Argentina